1999
DOI: 10.1021/ac981437g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rh, Pd, and Pt in Polar and Alpine Snow and Ice by Double-Focusing ICPMS with Microconcentric Nebulization

Abstract: The performance of a double-focusing inductively coupled plasma mass spectrometer equipped with a microconcentric nebulizer was investigated for the direct simultaneous determination of Rh, Pd, and Pt in less than 1 mL of melted snow and ice samples originating from remote sites. Ultraclean procedures were adopted in the laboratories and during the pretreatment steps, to avoid possible contamination problems. Spectroscopic and nonspectroscopic interferences affecting the determination of Rh, Pd, and Pt were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 30 publications
0
51
2
1
Order By: Relevance
“…Pt, Pd, and Rh were measured by ICP-SFMS with microconcentric nebulization, using a Finnigan Mat Element instrument (Finnigan, Bremen), as described in detail in ref 22. This technique, thanks to the extremely low noise signal and the very high ion transmission, is very attractive for ultratrace determination in environmental matrices (26,27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pt, Pd, and Rh were measured by ICP-SFMS with microconcentric nebulization, using a Finnigan Mat Element instrument (Finnigan, Bremen), as described in detail in ref 22. This technique, thanks to the extremely low noise signal and the very high ion transmission, is very attractive for ultratrace determination in environmental matrices (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…This technique, thanks to the extremely low noise signal and the very high ion transmission, is very attractive for ultratrace determination in environmental matrices (26,27). In particular, it was recently demonstrated that snow and ice, due to the high purity of the matrix, are well suited for direct PGMs determination (21,22,28 as three times the standard deviation of the blanks, were 0.008, 0.08, and 0.02 pg/g for Pt, Pd, and Rh, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in the tables and figures for each sample correspond to the average of five scanned lines. 6,10,27,28 Interferents were measured but they are not a problem here owing to the relatively high PGE levels in the catalysts and the lower oxide interference when using laser ablation. 29,30 …”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…These particles are most dangerous to people suffering from various respiratory tract diseases (e. g., asthma). Aerosol particles due to their toxicity are dangerous both to people living near the pollution sources and those who live farther because the finest particles are transported with air masses over long distances [1][2][3]. Therefore, the pollution emitted by anthropogenic sources becomes the problem not only of a separate town but also of a country, and thereby it is a global problem.…”
Section: Introductionmentioning
confidence: 99%